2014
DOI: 10.1109/lpt.2013.2291965
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength Conversion of a 9.35-Gb/s RZ OOK Signal in an InP Photonic Crystal Nanocavity

Abstract: Wavelength conversion of a 10-Gb/s (9.35 Gb/s net rate) return-to-zero ON-OFF keying signal is demonstrated using a simple InP photonic crystal H0 nanocavity with Lorentzian line shape. The shifting of the resonance induced by the generation of free-carriers enables the pump intensity modulation to be transferred to a continuous-wave probe with a sufficiently high quality so that the converted signal can be detected with a conventional telecommunication receiver. A clear eye diagram is observed for the convert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…5(b), the BER increases somewhat, but is still well below the threshold for employing forward error correction (FEC) schemes. Compared with a traditional Lorentzian structure [11], we find that patterning effects are significantly suppressed and the energy consumption is reduced, enabling modulation rates higher than the carrier relaxation rate. This speed enhancement originates from the regeneration characteristics of the nonlinear transfer function of the Fano resonance.…”
Section: Device Desginmentioning
confidence: 86%
“…5(b), the BER increases somewhat, but is still well below the threshold for employing forward error correction (FEC) schemes. Compared with a traditional Lorentzian structure [11], we find that patterning effects are significantly suppressed and the energy consumption is reduced, enabling modulation rates higher than the carrier relaxation rate. This speed enhancement originates from the regeneration characteristics of the nonlinear transfer function of the Fano resonance.…”
Section: Device Desginmentioning
confidence: 86%
“…[10]. The interest in the PhC/InP approach has been confirmed by the recent results from DTU, who demonstrated all-optical signal processing [13] and LPN, who introduced hybrid Silicon-InP cavities and demonstrated fast processing [14]. In Fig.5, we show the device and the signals used to drive it: the control signal comes from a prototype modelocked diode laser build by Alcatel-Lucent-Thales III-V labs operating at 10 GHz and providing 2 ps long pulses.…”
Section: Towards Optical Signal Processing Using Nanophotonic Camentioning
confidence: 86%
“…An estimated extinction ratio of 10 (7) dB is obtained at 10 (20) Gbit/s for an energy consumption of 76 (148) fJ/bit. Compared with a traditional Lorentzian structure [9], we find that patterning effects are significantly suppressed, enabling modulation rates higher than the carrier relaxation rate. This speed enhancement originates from the regeneration characteristics of the nonlinear transfer function of the Fano resonance [6].…”
mentioning
confidence: 76%
“…In that work it was also found that the nonmonotonous frequency dependence of the Fano transmission spectrum implies an inherent reduction of patterning effects. In contrast, a Lorentzian spectrum, with its monotonously varying tails, faithfully converts (slow) dynamics of the resonance shift into amplitude modulation, limiting the bitrate due to the long carrier lifetime [7][8][9][10][11].Here we experimentally demonstrate that by breaking the symmetry of a Fano structure, the switching properties can be further improved. Furthermore, by employing a nanocavity of the H0-type, which has the smallest mode volume of all known PhC defect cavities [2], we are able to further decrease the switching energy.…”
mentioning
confidence: 82%
See 1 more Smart Citation